Effect of varying machine ground pressure and traffic frequency on the physical properties of clay loam soils located in mountainous forests. Issue 3 (1st September 2016) - Solgi, Ahmad; Naghdi, Ramin; Labelle, Eric R.; Tsioras, Petros A.; Nikooy, Mehrdad
ABSTRACT: The aim of this study was to (a) assess the impact of two tractors (light and heavy) with different tire sizes and axle loads on forest soil physical properties and rut formation when subjected to different traffic frequencies, and (b) determine the relationships between the exerted ground pressure and soil bulk density. Treatments included five different traffic frequencies of the two tractors operated on two machine-operating trails with almost identical soil moisture content (20% in skidder trail and 21% in agricultural tractor trail). The light (Massey Ferguson 285) and heavy (Timberjack 450C) tractors were equipped with 750–18 and 24.5–32 single tires at the front and 18.4–30 and 24.5–32 single tires on the rear axle, respectively. The nominal ground pressures for the light and heavy tractors were 143.9 and 251.1 kPa at the front and 46.9 and 209.2 kPa at the rear axle, respectively. Bulk density in undisturbed areas ranged between 0.68 and 0.71 g cm −3 . In topsoil, one, three, five, and 10 passes of a light tractor caused mean bulk density values of 0.83, 0.98, 1.14, and 1.29 g cm −3 respectively, while values for the heavy tractor inducing the same number of passes were 0.92, 1.15, 1.34, and 1.48 g cm −3, respectively. Total porosity and macroporosity decreased considerably as both the number of passes and ground pressure increased. Ruts created by heavy tractor were, in all cases, deeper than the ones generated with the light tractor. Results indicated that traffic frequency and ground pressure had strong effects on the tested soil physical properties.